Drug abuse in Thimphu ([Thimphu] : [Royal Thimphu College], 2017)
Spiral-bound xerographic copy.
Student research project for BA, Political Science(Capstone Project):(2017).
Includes bibliographical references.
Keywords: Drug abuse -- Surveys; Drug use -- Bhutan; Capstone Project